Actividades físico-recreativas como alternativa para promover el buen uso del tiempo libre en niños de 9-10 años Loja, 2023 - Morocho Vicente, Evelyn Romina (2023)
The present work of curricular integration aims to evaluate the influence of physical-recreational activities in the use of free time of children from 9 to 10 years old in the Calasanz Fiscomisional High School during the period 2023. To achieve this, a mixed study was carried out combining quantitative and qualitative elements, using a correlational and descriptive approach, with a quasi-experimental design. The research began by applying an initial survey to the students to find out their preferences regarding the different physical-recreational activities, the results revealed that 92% of the participants preferred physical-recreational activities to be carried out through a program that promoted the good use of free time, while the remaining 8% disagreed with this proposal. Based on these results, a pedagogical proposal of physical-recreational activities for the good use of free time was implemented, which consisted of ten physical-recreational activity plans aimed at providing guidelines on how to use free time through different physical, recreational and tourist activities in a safe and educational manner. Once the proposal was implemented, an observation form was applied to the sample of 37 students, the results obtained showed significant progress in the use of free time, as well as a greater acquisition of knowledge about the types of physical-recreational activities available. In conclusion, the implementation of an educational program focused on these activities allowed the students to take advantage of their free time in a more meaningful way, which fostered their physical, recreational and tourism development. These results highlight the importance of continuing to promote this type of initiatives to improve the quality of life of children and to promote a comprehensive education that covers all relevant aspects of their growth and formation. Key words: physical activities, recreational activities, free time, development, integral education.